Pemberdayaan Masyarakat melalui Program Ketahanan Pangan dengan Beternak Ayam Kampung Petelur dan Partisipasi Masyarakat Guna Meningkatkan Ketahanan Pangan di Desa Pangkalbuluh (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Food security is a strategic issue related to meeting the basic needs of the community, in terms of availability, affordability, and sustainability. This study aims to describe community empowerment through a native chicken breeding program as an effort to improve food security in Pangkal Buluh Village, South Bangka Regency. The method used is a participatory approach that involves the community directly from the planning, socialization, training, implementation, to program evaluation stages. A total of 50 residents were involved as program targets, and each received four chicks, bringing the total number of chickens distributed to 200 native laying hens. The results showed enthusiasm and active participation from the community, both in attending training and in raising the chickens. The use of home yards as coops and local feed proved effective in reducing maintenance costs. This program has had a positive impact on the social aspect through the formation of livestock groups, the economic aspect with the potential for additional income from egg sales, and the food security aspect in the form of the availability of animal protein at the household level. Thus, the native laying hen breeding program can be a model for sustainable community empowerment in strengthening village food security.